2007
DOI: 10.1289/ehp.9432
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Blood Lead Levels Associated with Use of Chloramines in Water Treatment Systems

Abstract: BackgroundMore municipal water treatment plants are using chloramines as a disinfectant in order to reduce carcinogenic by-products. In some instances, this has coincided with an increase in lead levels in drinking water in those systems. Lead in drinking water can be a significant health risk.ObjectivesWe sought to test the potential effect of switching to chloramines for disinfection in water treatment systems on childhood blood lead levels using data from Wayne County, located in the central Coastal Plain o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 47 publications
2
56
1
Order By: Relevance
“…Other studies [3][4][5] have reported that the change in the BLL-reading score relationship is not linear. Like Miranda et al' s 8 observations of end-of-grade test scores, the magnitude of the difference in fall PALS-K scores associated with lead exposure in our study was similar to the difference associated with eligibility for free and reduced lunch, a measure of low SES.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Other studies [3][4][5] have reported that the change in the BLL-reading score relationship is not linear. Like Miranda et al' s 8 observations of end-of-grade test scores, the magnitude of the difference in fall PALS-K scores associated with lead exposure in our study was similar to the difference associated with eligibility for free and reduced lunch, a measure of low SES.…”
Section: Discussionsupporting
confidence: 87%
“…2 Crosssectional and longitudinal studies have revealed significant effects of lead exposure on learning with the use of standardized school tests and functional measures of school performance, including reading and math test scores, reading at grade level, and graduation from high school. [3][4][5][6][7][8] This evidence is reflected in Centers for Disease Control and Prevention' s recent establishment of a population-based reference value to target children with blood lead levels (BLLs) above the 97.5th percentile, which is currently a BLL of 5 mg/dL. 9 Learning to read is critical to the entire process of formal education.…”
mentioning
confidence: 99%
“…Public health departments recognized the advantages of GIS in screening, exposure prediction, and mapping cases. Using BLL data for lead poisoning, an increasing number of GIS-based ecological studies have identified risk factors as socioeconomic status (SES) [9][10][11][12][13][14][15][16][17][18]21], year built of housing [7][8][9][10][11]13,[15][16][17][18]20,21,23,28], race [11,13,14,16,17,21,23,27,28] and ethnicity [15,16,18].…”
Section: Ecological Studies and Gis Use In Childhood Lead Poisoningmentioning
confidence: 99%
“…At the data preparation stage, address geocoding is the most used tool to transfer tabular data sets, such as screened children addresses, into GIS [7][8][9][10][11][12][13][14][15][16][17][18][19]23]. Various GIS functions were used for multivariate mapping of BLLs and risk factors in a limited custom such as linking SES data with screened data records [49,50], map overlays [51,52], distance calculations [53], and hyperlinks to demolishing sites' photos and city maps for mapping dust-fall lead loadings [54].…”
Section: Ecological Studies and Gis Use In Childhood Lead Poisoningmentioning
confidence: 99%
“…Water companies are continuously reviewing their water treatment processes, and this may require review of the technology in use in dialysis units. For example, chlorine is being replaced by chloramines and monochloramine can increase the amount of bioavailable lead by interacting with domestic water piping [7] .…”
Section: Clinical Impact Of Water Qualitymentioning
confidence: 99%